1997
DOI: 10.1111/j.1834-7819.1997.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of die‐Spacidng on post‐cementation crown elevation and retention

Abstract: This paper reviews the relevant dental literature concerning the effect of die-spacing on crown elevation and pre-and post-cementation crown retention. Techniques of providing die-spacing and measurement of the thickness of die-spacer are discussed. A review of the role of the provision of a cement space in reducing post-cementation crown elevation is presented. Factors which may affect crown retention prior to and following cementation are also reviewed. The influence of variables in techniques and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 36 publications
3
32
0
5
Order By: Relevance
“…Eames et al 1 reported a 25% increase in retention when comparing 0 μm to 25 μm die spacer thickness. This improved retention was supported by Carter and Wilson, 2 who reported that retention increased from 250 N to 375 N as die spacer thickness changed from 0 to 8 layers. In contrast, Jorgensen and Esbensen 16 reported a moderate association between film thickness and retention, while Vermilyea et al 17 reported a 32% reduction in retention when comparing 0 with 2 layers of Tru-Fit paint on die spacer (George Taub Products and Fusion Co Inc).…”
supporting
confidence: 57%
“…Eames et al 1 reported a 25% increase in retention when comparing 0 μm to 25 μm die spacer thickness. This improved retention was supported by Carter and Wilson, 2 who reported that retention increased from 250 N to 375 N as die spacer thickness changed from 0 to 8 layers. In contrast, Jorgensen and Esbensen 16 reported a moderate association between film thickness and retention, while Vermilyea et al 17 reported a 32% reduction in retention when comparing 0 with 2 layers of Tru-Fit paint on die spacer (George Taub Products and Fusion Co Inc).…”
supporting
confidence: 57%
“…37 Thus, retentive preparations, which are long, near parallel and have a large surface area, are most at risk of not seating fully. This problem can be overcome by die spacing and controlled cement application or by venting the crown.…”
Section: Resin Cementsmentioning
confidence: 99%
“…The increased cement space results in more rapid seating with decreased deformation of the restoration. [39][40][41] Die spacing results in a slightly loose fit of a crown on its preparation, but its effect on retention is unclear with some studies reporting an increase in retention 37 while others report a decrease or no effect. A recent study concluded that decreasing the width of the cement layer increases the resistance to dynamic lateral loading.…”
Section: Resin Cementsmentioning
confidence: 99%